Contribution of rs1799998 polymorphism in CYP11B2 gene in susceptibility to preeclampsia - Kaio Raffael Valotta Bezerra; Sarah Cristina Sato Vaz Tanaka; Vanessa Resende Souza Silva; Marina Carvalho Paschoinni; Roseane Lopes da Silva Grecco; Fernanda Caroline Soardi; Marly Aparecida Spadotto Balarin
Abstract Objectives: the present study aimed to evaluate the association between the rs1799998 polymorphism of the CYP11B2 gene and the susceptibility to preeclampsia (PE) in a Brazilian population. Methods: the study group comprised 61 women who were diagnosed with PE. The control group included 116 women who did not show changes in their blood pressure levels during their pregnancies. The rs1799998 polymorphism of the CYP11B2 gene was amplified by allele-specific polymerase chain reaction (PCR). A multiple logistic regression analysis was performed using the SNPStat program to evaluate the risk of the CYP11B2 gene rs1799998 polymorphism contributing to PE. Results: the PE group had the following genotypes: 1.64% CC, 91.80% CT, and 6.56% TT. In the control group, the observed genotypic frequencies were: 11% CC, 73% CT, and 16% TT. The genotypic frequency distribution did not fit the Hardy Weinberg Equilibrium (HWE) in either study group. The multiple logistic regression analysis showed a statistically significant difference for the rs1799998 polymorphism in the recessive model. Conclusion: the results suggest an association between the recessive model of C/C genotype of the rs1799998 polymorphism of the CYP11B2 gene and susceptibility to PE.